An Estimation of Efficiency of Expenditure for Payment - Subačienė, Rasa (Ekonomika, 2001)
The article investigates an estimation of efficiency of labour cost on a basis of 21 enterprise of manufacturing. The author of this article offers some indices to estimate the efficiency of labour cost. In order to research the profit rate of enterprises and to setimate their performance’s efficiency several ratios profit 10 income are used. Materials cost and services make a major part of goods sold, but the control process of this expenditures is not very flexible. There are presented a survey of some ratios of profit to income and the way, how to modicify them into earning of income and optimum limits of payment and expenditures ratios.